The Impact of Digital Transformation on Innovativeness in Airline Companies: The Role of Agility and Openness to Change - Yıldız, Bülent; Mazıoğlu, Volkan (Journal of Aviation, 2025)
This study aims to analyze the mediating role of organizational agility and the moderating role of openness to change by examining the impact of digital transformation on organizational innovativeness in airline companies. The airline industry, characterized by its dynamic nature and intense competitive conditions, necessitates continuous change and innovation. The dynamic nature of the airline industry due to intense competition, high safety standards and ever-changing technological requirements necessitates the rapid adaptation of digital transformation. In this context, understanding how digital transformation influences the innovative capacities of businesses, as well as the significance of organizational factors such as agility and openness to change in these processes, holds substantial theoretical and practical value. This research aims not only to generate theoretical insights but also to provide practitioners in the airline industry with recommendations for optimizing digital transformation processes, enhancing innovation capacities, and achieving competitive advantages. In line with the data collected from 421 airline employees through a questionnaire, it was determined that organizational agility plays a full mediating role in the relationship between digital transformation and innovation and openness to change strengthens this process. Research findings show that agile organizations benefit more from digital transformation, and firms open to change have higher innovation capacities. Accordingly, airline companies recommend strategies to increase organizational agility, encourage employees' openness to change and expand digital skills training to manage digital transformation processes effectively. Furthermore, it is emphasized that digitalization should be considered a strategic transformation in terms of operational efficiency and in the context of corporate governance, decision-making processes and customer experience.
Keywords: İşletme; Digital Transformation; Innovation; Agility; Openness to Change; Business Administration